Computer-Aided Tuberculosis Detection from Chest X-Ray Images with Convolutional Neural Networks - Evalgelista, Lucas Gabriel Coimbra; Guedes, Elloá B. (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2018: Anais do XV Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2018.4444, 2018)
Diagnosing Tuberculosis is crucial for proper treatment since it is one of the top 10 causes of deaths worldwide. Considering a computer-aided approach based on intelligent pattern recognition on chest X-ray with Convolutional Neural Networks, this work presents the proposition, training and test results of 9 different architectures to address this task as well as two ensembles. The highest performance verified reaches accuracy of 88.76%, surpassing human experts on similar data as previously reported by literature. The experimental data used comes from public medical datasets and comprise real-world examples from patients with different ages and physical characteristics, what favours reproducibility and application in practical scenarios.